(a) n + 5 = 19 (n = 1)
Answers
Answered by
1
Answer:
n - 19 ( n = 1 ) = - 5
Step-by-step explanation:
subtract 5 from both the side of the equation
n + 5 = 19 ( n = 1 )
n + 5 - 5 = 19 ( n = 1 ) -5
n = 19 ( n = 1 ) - 5
n = 19 ( n=1) -5
n+19(n=1) (-1) = 19 ( n=1)-5-1
n-19( n =1) = -5
Answered by
2
Answer:
=>
Step-by-step explanation:
Given that:-
To find:- The value of ,
Now, multiply with the bracket term:
=>
=>
Combining the like terms,
=>
Simplifying it further, we get
=>
Divide by on both sides,
=>
By reducing it to its lowest term,
=>
Hence, the required solution is
Similar questions